ANTI-BACTERIAL ACTIVITY TEST OF ETHANOL EXTRACT, N-HEXANE FRACTION, ETHYL ACETATE FRACTION AND WATER FRACTION FROM DRAGON FRUIT STEM (Hylocereus polyrhizus) AGAINST METHICILLIN-RESISTANT Staphylococcus aureus (MRSA) - Indah Indah Sulistyarini; Diah Arum Sari; Muhammad Ryan Radix Rahardian (Universitas Muhammadiyah Kalimantan Timur, 2021)
The stems of red dragon fruit (Hylocereus polyrhizus) are known to have several antibacterial compounds. The purpose of this study was to determine the antibacterial activity of ethanol extract, n-hexane, ethyl acetate, and water fractions from dragon fruit stems on the growth of Methicillin-resistant Staphylococcus aureus (MRSA), and to determine the types of compounds that are antibacterial. The data on the greatest antibacterial activity was found at a concentration of 30% both in the ethanol extract (1,850cm); n-hexane fraction (1,948 cm); ethyl acetate fraction (1,640 cm) and water fraction (0.884 cm). Meanwhile, the results of contact bioautography showed that the antibacterial compounds of Methicillin-resistant Staphylococcus aureus (MRSA) were flavonoids, saponins, and steroids.